Synthesis of manganese oxide nanoparticles from hydrothermal method as electrode material for high performance supercapacitor applications - Thean, Jie Min (Nanyang Technological University, 2022)
With the expansion of modern technology and the depletion of fossil fuels, new energy storage systems are required. Lithium-ion batteries, which are believed to be a promising energy source, are unable to match the rising need for increased power density, and the Earth's crust has a finite supply of Li. As a result, supercapacitors are required to tackle the energy crisis, and they are made of earth-friendly, non-toxic materials. Manganese oxide (Mn3O4) has so far been identified as a viable supercapacitor electrode material. In this project, Mn3O4 nanoparticles were synthesized via hydrothermal reaction from Mn(NO3)2 at varying durations and temperatures. Through this eco-friendly and easy-to-execute synthesis, relatively high purity Mn3O4 particles were formed. The morphology and crystallinity were then studied via Scanning Electron Microscope (SEM) and X-Ray Diffraction (XRD) respectively. Thereafter, the Mn3O4 sample was then deposited on activated carbon paper. The electrochemical characteristics were investigated utilizing a three-electrode cell setup using cyclic voltammetry (CV) and galvanostatic charge-discharge (GCD) profiles. Finally, a study was evaluated to determine how the varying temperature and time of the hydrothermal process affects the shape and electrochemical properties of Mn3O4.